2013
DOI: 10.21273/hortsci.48.5.657
|View full text |Cite
|
Sign up to set email alerts
|

‘NuMex Heritage Big Jim’ New Mexican Chile Pepper

Abstract: Pepper Breeding and Genetics Program announces the release of 'NuMex Heritage Big Jim' chile pepper (Capsicum annuum L.). 'NuMex Heritage Big Jim' is an openpollinated, improved, New Mexican pod-type cultivar. The name was chosen to distinguish the newly selected cultivar from the original cultivar, NuMex Big Jim, while retaining its association. 'NuMex Heritage Big Jim' has superior flavor, a uniform and higher heat level, greater plant and pod uniformity, and higher yield as compared with the current commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The NMSU C. annuum complex separated into subgroups based on fruit type, consistent with previous observations among Spanish C. annuum pepper genotypes [31]. Breeding and selection for improvement of heirloom cultivars including 'NuMex Big Jim' and 'NuMex Sandia' have resulted in the release of the 'NuMex Heritage Big Jim' and the 'NuMex Sandia Select', with both cultivars having increased consumer and horticultural value [38,39]. Genotyping using genomewide SNP markers showed that these improved heirloom cultivars did not necessarily cluster with the parental heirlooms, albeit still observed to be closely related varieties.…”
Section: Genetic Relatedness In New Mexican Chile Pepper Germplasmsupporting
confidence: 87%
See 1 more Smart Citation
“…The NMSU C. annuum complex separated into subgroups based on fruit type, consistent with previous observations among Spanish C. annuum pepper genotypes [31]. Breeding and selection for improvement of heirloom cultivars including 'NuMex Big Jim' and 'NuMex Sandia' have resulted in the release of the 'NuMex Heritage Big Jim' and the 'NuMex Sandia Select', with both cultivars having increased consumer and horticultural value [38,39]. Genotyping using genomewide SNP markers showed that these improved heirloom cultivars did not necessarily cluster with the parental heirlooms, albeit still observed to be closely related varieties.…”
Section: Genetic Relatedness In New Mexican Chile Pepper Germplasmsupporting
confidence: 87%
“…These varieties possess different fruit (pod) types such as New Mexican, paprika, cayenne, jalapeno, and included the ornamental chile peppers speci cally developed for the potted plant and nursery industries [47], all belonging to C. annuum. The New Mexican types included 'NuMex Joe E. Parker' [48], 'NuMex Heritage Big Jim' [38], 'NuMex Big Jim' [49], and 'NuMex Sandia Select' [39], whereas the cayenne type included 'NuMex Las Cruces' [50]. The paprika type consisted of 'NuMex Garnet' [51], and the jalapenos comprised of 'NuMex Jalmundo' [52], 'NuMex Vaquero' [53], and 'NuMex Piñata' [54].…”
Section: Methodsmentioning
confidence: 99%
“…The NMSU C. annuum complex separated into subgroups based on fruit type, consistent with previous observations among Spanish C. annuum pepper genotypes [ 31 ]. Breeding and selection for improvement of heirloom cultivars including ‘NuMex Big Jim’ and ‘NuMex Sandia’ have resulted in the release of the ‘NuMex Heritage Big Jim’ and the ‘NuMex Sandia Select’, with both cultivars having increased consumer and horticultural value [ 38 , 39 ]. Genotyping using genome wide SNP markers showed that these improved heirloom cultivars did not necessarily cluster with the parental heirlooms, albeit still observed to be closely related cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…green pod with a relatively high heat level and increased yield. A similar request was given for 'New Mexico 6-4' and 'NuMex Big Jim', which culminated in the release of 'NuMex Heritage 6-4' and 'NuMex Heritage Big Jim' (Bosland, 2012;Bosland and Coon, 2013).…”
mentioning
confidence: 94%